Realization of a Virtual Lambda Sensor on a Fixed Precision System - Amato, P.; Cesario, N.; Meglio, M. Di; Pirozzi, F. (Design, Automation and Test in Europe, 2005)
The aim of this work is to study the implementation feasibility of a VLS (Virtual Lambda Sensor) by a TSK (Takagi, Sugeno, Kang) singleton FIS (Fuzzy Inference System). Such a sensor could be used in a model based EMS (Engine Management System) for trade gasoline engines. FIS design target is to obtain a system with a fixed data representation (i.e. 10 bit)and a limited number of inputs, outputs, rules and membership.